Adaptive Governance in The Bantul Regency Regional House of Representatives (DPRD) in Responding to Regional Strategic Issues - Titis Ajeng Ganis Mareti; Ulul Albab; Dian Ferriswara (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the adaptive governance practices implemented by the Bantul Regency Regional House of Representatives (DPRD) in responding to various strategic regional issues. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with the DPRD Speaker, commission members, the DPRD Secretary, Secretariat officials, and representatives from regional government agencies, supplemented by observations of the legislative process and document analysis. Data analysis utilized the interactive model developed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing and verification. The findings indicate that the Bantul Regency DPRD’s adaptive capacity is manifested through flexibility in legislative agenda-setting, continuous institutional learning, and multi-stakeholder collaboration at every stage of the policy process. Collaboration with the local government, academics, civil society organizations, the media, and the public contributes to higher-quality decision-making thatis more responsive and participatory. The study also identified several challenges, namely political dynamics among stakeholders, limited inter-institutional data integration, and suboptimal continuous policy evaluation. Based on these findings, the study develops an adaptive governance model consisting of five dimensions: adaptive leadership, institutional learning, decision-making flexibility, multi-stakeholder collaboration, and feedback-based policy evaluation. This research extends the application of the adaptive governance concept to local legislative bodies and offers practical implications for strengthening DPRD governance to make it more adaptive, responsive, and sustainable in the face of changing strategic environments.